Salatiga Tempo Dulu: Membongkar Lapisan Sejarah Kota Tertua di Jawa Tengah - arvanida heradita rafsanjani (Historia Pedagogia, 2024)
Abstrak  Salatiga as one of the oldest cities in Central Java has a deep history from the colonial era to modern development. The city initially developed as an important administrative and economic center under Dutch colonial rule, with many colonial architectural monuments still standing today. Research in Salatiga aims to explore the social, cultural, and political dynamics that shape   the city's identity through various methods, such as literature studies, interviews with community leaders, and archaeological analysis. Its strategic location between Semarang and Solo also strengthens its historical role as a communication and operational center in the region.